The Relationship Of The Characteristics Of The Mother With The Type Of Delivery - Laila Rahmi; Lusiana El Sinta Bustami (Faculty of Medicine, Universitas Andalas, 2021)
The incidence of deliveries by cesarean section is reported to have increased worldwide and exceeded the range recommended by the World Health Organization (WHO) which is 10-15% as an effort to save the lives of mothers and babies. Latin America and the Caribbean region were the highest contributors at 40.5%. Riskesdas data in 2018 shows that the prevalence of delivery by caesarean section in Indonesia is 17.6%. This type of research is cross sectional with secondary data sources. The study was conducted from May to November 2021 at the Padang City Government and Private Hospital. The population was all mothers who gave birth during the survey period from January 1 to December 31, 2020 at hospitals in the city of Padang (dr. Reksodiwiryo Hospital, Andalas University Hospital, and Ibu Sina Islamic Hospital) with samples of all populations that met the inclusion and exclusion criteria. Data were collected in a data collection format, analyzed by univariate analysis and bivariate analysis. Most (82.7%) deliveries were performed by cesarean section, a small percentage (23.2%) were high risk mothers (< 20 years and > 35 years), a small percentage (37.9%) gave birth to their first child. and more than 4 children, a small percentage (18.6%) of maternity mothers had education at the middle school level and below, there was a relationship between maternal age and the type of delivery performed, and there was no relationship between parity and maternal education with the type of delivery performed. Health workers, especially midwives, are expected to further improve health promotion related to the impact and dangers of sectio caesarea with non-medical indications and increase the provision of midwifery care to pregnant women to optimize the position of the fetus so that mothers can give birth normally vaginally